A PI polyamide–TPP conjugate targeting a mtDNA mutation induces cell death of cancer cells with the mutation. Issue 6 (2nd May 2021) - Koshikawa, Nobuko; Yasui, Nanami; Kida, Yuki; Shinozaki, Yoshinao; Tsuji, Kohei; Watanabe, Takayoshi; Takenaga, Keizo; Nagase, Hiroki
Abstract: Mitochondrial DNA (mtDNA) mutations occur frequently in cancer cells, and some of them are often homoplasmic. Targeting such mtDNA mutations could be a new method for killing cancer cells with minimal impact on normal cells. Pyrrole‐imidazole polyamides (PIPs) are cell‐permeable minor groove binders that show sequence‐specific binding to double‐stranded DNA and inhibit the transcription of target genes. PIP conjugated with the lipophilic triphenylphosphonium (TPP) cation can be delivered to mitochondria without uptake into the nucleus. Here, we investigated the feasibility of the use of PIP‐TPP to target a mtDNA mutation in order to kill cancer cells that harbor the mutation. We synthesized hairpin‐type PIP‐TPP targeting the A3243G mutation and examined its effects on the survival of HeLa cybrid cells with or without the mutation (HeLamtA3243G cells or HeLamtHeLa cells, respectively). A surface plasmon resonance assay demonstrated that PIP‐TPP showed approximately 60‐fold higher binding affinity for the mutant G‐containing synthetic double‐stranded DNA than for the wild‐type A‐containing DNA. When added to cells, it localized in mitochondria and induced mitochondrial reactive oxygen species production, extensive mitophagy, and apoptosis in HeLamtA3243G cells, while only slightly exerting these effects in HeLamtHeLa cells. These results suggest that PIP‐TPPs targeting mtDNA mutations could be potential chemotherapeutic drugs to treat cancers without severe adverse effects. Abstract : Pyrrole‐imidazole polyamide (PIP) conjugated with triphenylphosphonium (TPP) targeting mtDNA mutations induced extensive mitophagy and apoptosis in cancer cells harboring the mutation. Thus, they could be potential chemotherapeutic drugs to treat cancers.